Experimental cyclic performance of cold-formed steel bolted moment resisting frames. (15th February 2019) - McCrum, Daniel P.; Simon, Jordan; Grimes, Michael; Broderick, Brian M.; Lim, James B.P.; Wrzesien, Andrzej M.
Highlights: Cyclic testing of cold-formed steel portal frames. Perfect-fit and normal tolerance bolt hole connection types investigated. Good seismic performance through ductility and energy dissipation capacity. Normal tolerance bolt hole connection has greater ductility and energy dissipation capacity. Bi-moment should be considered by designers as it is the second largest stress after major axis bending. Abstract: This paper investigates the seismic performance of a single storey moment resisting cold-formed steel (CFS) portal frame through cyclic testing. Six monotonic and six cyclic tests were performed on three different section sizes of CFS. The portal frames were 3.2 m long × 2.2 m high and the CFS sections bolted with either perfect-fit tolerance bolt holes (PTBH) or normal tolerance bolt holes (NTBH) connections. Connections with NTBH are standard in CFS, but connections with PTBH are often only used for short-spanning frames. Results from the tests demonstrated that both PTBH and NTBH connections had stable hysteresis and good hysteretic energy dissipation capacity and ductility. On average, the NTBH connections performed better under cyclic loading in comparison to the PTBH connections (5.4% larger ductility and 22.3% increased energy dissipation). Strain gauge results show failure due to combined bending and bi-moment stresses, of which the bi-moment stress component accounted for 41% of the total longitudinal stresses at the section web. It should be noted that bi-moment stresses are often incorrectly ignored by practitioners; the experimental test results thus show that by doing so the sections would fail at 59% of the design moment. Initial failure was localised at the top of the column sections in the form of local buckling at the web-to-flange junction under compressive stresses. Several load cycles past the initial buckling stage led to a further reduction of steel ductility due to strain hardening and strain ageing leading to fracture of the steel in the section corners. The buckling/tearing failure in the columns would result in a reduced axial load carrying capacity.